STRATEGI PENGGUNAAN DANA DESA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT MELALUI KEGIATAN BUM DESA PASTI JAYA ABADI DESA PASTI JAYA - Shanti Veronica br Siahaan; Yeremia Niaga Atlantika (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This research was conducted aiming to find out what factors influence the decision of Village Government in allocating Village Funds and to find out strategies for using Village Funds to support the development of the Village economy through BUMDesa Pasti Jaya Abadi Pasti Jaya activities. The research method used is a descriptive qualitative research approach with sources selected by purposeful sampling, namely the Village Government, Director, Secretary and Treasurer of BUMDesa, management of BUMDesa business units where researchers participate in research by collecting data by means of observation, in-depth interviews. by meeting in person or through Whatsapp media and cell phones as well as documentation of BUMDesa activities. The results of this study indicate that the main factor influencing the decision to use Village Funds in Pasti Jaya Village in 2020-2022 is the Central Government Regulation on the use of Village Funds during the Covid-19 pandemic. While the strategy for using Village Funds in improving the village economy through BUMDes activities is to meet local market demand through the BRILINK program, based on the potential of local resources through the SAPRODI business unit, capital to help micro-enterprises through productive business credit units and post-harvest processing through flour production business units. corn rice. BUMDes through the activities of business units that have been running have been able to provide PADes since 2018 and participate in improving the welfare of rural communities.